TOKSISITAS EKSTRAK TERPURIFIKASI DAUN BUAS-BUAS (PREMNA SERRATIFOLIA L.) TERHADAP MORTALITAS LARVA NYAMUK CULEX SP. - Ulmiyatul Alifiah Zahroh; Dwi Wahyuni; Mochammad Iqbal (Saintifika, 2022)
Culex sp. is a vector of filariasis. Vector control mostly uses chemical insecticides which have a negative impact. Buas-buas plants (Premna serratifolia L.) are one of the plants that have the potential as an alternative to the use of chemical insecticides that have been widely used (as botanical insecticides). Buas-buas leaves (Premna serratifolia L.) contain alkaloids, flavonoids, saponins, and tannins. This study aimed to test the toxicity of the purified extract of buas-buas leaf (Lethal concentration 50) on the mortality of Culex sp. larvae with an exposure time of 24 hours. Serial concentrations of purified extract used were 850, 1350, 1850, 2350, and 2850 ppm with four repetitions. Each treatment used 20 Culex sp. late three to early four instars. Toxicity testing of Culex sp. gives an LC50 result of 1799.77 ppm.. Kata Kunci: Culex sp.; Premna serratifolia L. ; Terpurifikasi; Toksisitas